Liver Transplantation for Autoimmune Hepatitis: Infections are the Major Cause of Mortality - Danış, Nilay; Günşar, Fulya (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Danış N, Günşar F. Liver transplantation for autoimmune hepatitis: Infections are the major cause of mortality. Turk J Gastroenterol. 2025;36(3):133-134.